A study of Women’s role in political parties in East and West Telangana (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In order to shape equitable government and democratic representation, women's engagement in political parties is vital. Women in India still encounter obstacles while trying to rise to positions of leadership within political parties, even though there are laws and policies in place to help them. Using an analysis of geographical differences, socio-political factors, and institutional hurdles, this research looks at the involvement of women in political parties in East and West Telangana. This article takes a look at the gender gap in leadership positions, the efficacy of party-led programs to empower women, and important trends in political activity by comparing these areas. It seems that traditional social conventions in West Telangana continue to restrict female political engagement, in contrast to East Telangana where women's participation is stronger as a result of urbanisation and education. More institutional backing, new policies, and a change in party structures to encourage women inclusion at all levels are necessary to overcome these obstacles.